Rabbis, Rebbes, and Roshei Yeshiva: Jewish Religious Leadership in Recent Graphic Novels. Issue 3 (2nd October 2018) - Reingold, Matt
ABSTRACT: This article analyzes the depictions of rabbis in James Sturm's Market Day, Harvey Pekar and JT Waldman's Not the Israel My Parents Promised Me, Joann Sfar's The Rabbi's Cat, and Sfar's Klezmer . Considered together, these four recent graphic novels present a fairly negative portrait of rabbinical leadership and of the impact rabbis can have on communities. This negative depiction reaffirms Zierler's earlier assertion about literary depictions of rabbis in American fiction. Beyond the focus on the genre of graphic novels, this essay considers the different literary rabbis in light of the historical and contemporary role of the rabbi and recognizes that within the Jewish community, three distinct models of religious leadership exist. These three models are then used to analyze the rabbinical representations to better understand how and why the rabbis are successful or unsuccessful in providing meaningful pastoral care.